(untitled)
A synthesis of mono nuclear bis indacene mono metal compound of type [L-M-L] where (L is 2,6- diethyl-4,8-dimethyl-1,5-dihydro-s-indacene, M=Pd. Pd-bis (ƞ5-2,6-diethyl-4,8-dimethyl-1,5- dihydro-s-indaceneide) [Pd (Ic’H)2], and the oligomeric form of this compound is successfully prepared. The prepared compound is of the type [L-M-L-M-L-M-L] where M= Pd and L =-2,6- diethyl-4,8-dimethyl-1,5-dihydro-s-indaceneide)